Atomistic modelling of crack-inclusion interaction in graphene. (15th May 2018) - Dewapriya, M.A.N.; Meguid, S.A.; Rajapakse, R.K.N.D.
Highlights: Atomic crack-inclusion interaction induces a complex stress state at the crack-tip. Inclusions can be used to tailor the crack-tip stress field. Existing continuum crack-defect models can be used to develop design envelopes. Inclusions of specific locations lead to a reduction in the fracture resistance. Abstract: In continuum fracture mechanics, it is well established that the presence of crack near an inclusion leads to a significant change in the crack-tip stress field. However, it is unclear how atomistic crack-inclusion interaction manifests itself at the nanoscale where the continuum description of matter breaks down. In this work, we conducted molecular dynamics simulations to investigate the interactions of an atomic-scale boron nitride inclusion with an edge crack in a graphene sheet. Numerical simulations of nanoscale tensile tests were obtained for graphene samples containing an edge crack and a circular inclusion. Stress analysis of the samples show the complex nature of the stress state at the crack-tip due to the crack-inclusion interaction. Results reveal that the inclusion results in an increase (amplification) or a decrease (shielding) of the crack-tip stress field depending on the location of the inclusion relative to the crack-tip. Our numerical experiments unveil that inclusions of specific locations could lead to a reduction in the fracture resistance of graphene. Results of the crack-inclusion interaction study were compared with the corresponding results of crack-hole interaction problem. The study also provides an insight into the applicability of well-established continuum crack-microdefect interaction models for the corresponding atomic scale problems.